A formação de professores indígenas na perspectiva da etnomatemática: - BASTOS, Juslainy dos Santos (Universidade Federal do Tocantins, 2023)
This study aims to present the contributions from dissertations and theses defended and published between the years 2005 to 2014 dealing with the training of indigenous teachers in mathematics education area. The research was based on bibliographic qualitative research approach in order to answer the following research question: Which terms of training of indigenous teachers dissertations and theses published in Mathematics Education area defended and published in the years 2005 to 2014 show pedagogical practices for teaching and learning of mathematics in and for training indigenous teachers? Like this, they were analyzed ten works including dissertations and theses Graduate Programs higher education institutions from different regions and states. Analyzes from the readings of these theses and dissertations highlight that researchers conducted their research in indigenous communities from the perspective of Ethnomathematics, highlighting in its work the different formation processes of indigenous teachers and how they occur teaching and mathematics learning in indigenous schools. As a starting point, this study evidence from references adopted by researchers that can be associated with a proposal for teacher training that involves the study of school mathematics with the everyday practices of teachers in order to provide other educational and pedagogical actions from the investigation of mathematical contexts existing indigenous practices.